PENGARUH ETOS KERJA, KOMPENSASI DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN (FKIP) UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Septiana Muslim (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
Every company would expect employees to give maximum results in their work. Therefore, the company / institution must try to do the actions that cause the employees to realize that expectation. One effort that can be done by the company is to find out what factors affect the improvement of employee performance, then take action to improve it. Many factors can affect employee performance improvement. These factors are work ethic, compensation and discipline. The type of data in this study is to use primary data. This research uses economic variables such as Work Ethic, Compensation, and Discipline. The analysis used is Descriptive analysis. The result of this research is variable of work ethic have an effect on to employee performance of FKIP UST, while discipline and compensation variable does not affect to employee performance of FKIP UST. As well as 49% of work ethic variables, compensation, and discipline affect together on the performance of FKIP UST employees, and the rest are described outside the model.